2021
DOI: 10.1177/0363546521989651
|View full text |Cite
|
Sign up to set email alerts
|

SCR 2021

Abstract: You're going out a youngster but you've got to come back a star.-James Seymour and Rian James, 42nd Street (1993)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 33 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…The disadvantages of using dermal allografts are the high associated cost and reports of reduced healing rates. 16 Dermal allograft appears to have the ability to integrate into bone, but histologic evaluations in a rat model suggested poor cellular organization and reduced strength compared with controls. 17 A study by Smith et al 18 suggested that dermal allograft had a worse ability to integrate into canine bone compared with a boneetendon allograft option.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The disadvantages of using dermal allografts are the high associated cost and reports of reduced healing rates. 16 Dermal allograft appears to have the ability to integrate into bone, but histologic evaluations in a rat model suggested poor cellular organization and reduced strength compared with controls. 17 A study by Smith et al 18 suggested that dermal allograft had a worse ability to integrate into canine bone compared with a boneetendon allograft option.…”
Section: Discussionmentioning
confidence: 94%
“…Thinner acellular dermal allografts 3 mm in thickness have been popularized because they avoid the harvest issues of autograft and are more readily available. 16 Graft preparation time is reduced as well. The disadvantages of using dermal allografts are the high associated cost and reports of reduced healing rates.…”
Section: Discussionmentioning
confidence: 99%